2011
DOI: 10.1002/adsc.201000698
|View full text |Cite
|
Sign up to set email alerts
|

A Complexation Promoted Organic N‐Hydroxy Catalytic System for Selective Oxidation of Toluene

Abstract: Complexation was innovatively utilized to design a novel catalytic system for the selective oxidation of toluene, which runs contrary to the traditional definition of organic metal complex catalysis. In the present system, an N-heteroaromatic ringcontaining N-hydroxy compound acts as the catalytically active component. Through an electron-withdrawing effect produced by the occurring complexation with proper metal salts, which was characterized by real-time in situ Fourier transform infrared spectra, the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…NHQI was synthesized by reaction of pyridine-2,3-dicarboxylic acid anhydride 37 with hydroxylamine hydrochloride following a procedure reported in the literature. 10 Toluene, ethylbenzene, cumene, p-xylene, p-methoxytoluene, miodotoluene, 4-methylacetophenone, p-tolunitrile, cyclohexane, adamantane, methanol, ethanol, 2-propanol, tetrahydrofuran, N,Ndimethylformamide, and p-chlorobenzaldehyde were commercially available at their highest purity and used as received.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHQI was synthesized by reaction of pyridine-2,3-dicarboxylic acid anhydride 37 with hydroxylamine hydrochloride following a procedure reported in the literature. 10 Toluene, ethylbenzene, cumene, p-xylene, p-methoxytoluene, miodotoluene, 4-methylacetophenone, p-tolunitrile, cyclohexane, adamantane, methanol, ethanol, 2-propanol, tetrahydrofuran, N,Ndimethylformamide, and p-chlorobenzaldehyde were commercially available at their highest purity and used as received.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Via this connection, Xia et al showed that the catalytic activity of NHQI in the aerobic oxidation of toluene is significantly higher than that of NHPI either in the absence or in the presence of a metal cocatalyst. 10 More recently, it was reported that NHQI, in combination with 4-carboxyl-N-hydroxyphthalimide, showed excellent activity in the aerobic oxidation of ethylbenzene. 11 In this study, we report the ultraviolet−visible (UV−vis) and electron paramagnetic resonance (EPR) spectroscopic characterization of QINO and a kinetic investigation of the HAT reactivity of QINO with a series of organic substrates, including aliphatic hydrocarbons, alkylaromatics, alcohols, ethers, aldehydes, and amides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3) led to a slightly lower conversion with comparable selectivity toward the formation of BAC (Run 5 and 6). When both Co(OAc) 2 and Mn(OAc) 2 were used, 15 the conversion increased but the selectivity for BAC was slightly decreased (Run 7).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the traditional NHPI/Co(OAc) 2 6 11 were also tested, however, poor conversions were observed (Run 15 and 16). The reaction in PEG 1000 -DIL (PEG 1000-based dicationic ionic liquid) resulted in slightly lower conversion and selectivity due to its lack of acidity (Run 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation